2021
DOI: 10.12998/wjcc.v9.i28.8327
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus and COVID-19: Understanding the association in light of current evidence

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections have posed a problematic healthcare situation worldwide since December 2019. Diabetes mellitus is associated with an increased risk and severity of coronavirus disease 2019 (COVID-19). While interacting with various other risk factors, high blood sugar was found to reduce immunity and increase the replication of SARS-CoV-2. Oxidative stress and the release of pro-inflammatory cytokines are greater in diabetic individuals than in healthy pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 69 publications
2
27
0
3
Order By: Relevance
“…High blood glucose has been demonstrated to decrease immunity and increase SARS-CoV-2 replication when combined with other risk factors. In diabetics, oxidative stress and the secretion of pro-inflammatory cytokines are higher than in individuals without DM, exacerbating the result of SARS CoV-2 infection[159].Diabetes, the most frequent endocrine condition, is a face in the "Endocrine phenotype" for COVID-19 since it is one of the most common comorbidities associated with mortality in COVID-19 patients. Most of the available data focused on glucose dysregulation during COVID-19 infection and the development of diabetes[158,159].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…High blood glucose has been demonstrated to decrease immunity and increase SARS-CoV-2 replication when combined with other risk factors. In diabetics, oxidative stress and the secretion of pro-inflammatory cytokines are higher than in individuals without DM, exacerbating the result of SARS CoV-2 infection[159].Diabetes, the most frequent endocrine condition, is a face in the "Endocrine phenotype" for COVID-19 since it is one of the most common comorbidities associated with mortality in COVID-19 patients. Most of the available data focused on glucose dysregulation during COVID-19 infection and the development of diabetes[158,159].…”
mentioning
confidence: 99%
“…In diabetics, oxidative stress and the secretion of pro-inflammatory cytokines are higher than in individuals without DM, exacerbating the result of SARS CoV-2 infection[159].Diabetes, the most frequent endocrine condition, is a face in the "Endocrine phenotype" for COVID-19 since it is one of the most common comorbidities associated with mortality in COVID-19 patients. Most of the available data focused on glucose dysregulation during COVID-19 infection and the development of diabetes[158,159]. Thus, individuals infected with SARS-CoV-2 should be given extra attention to the emergence of diabetes.Obesity, another metabolic, endocrine condition, increases vulnerability to severe SARS-CoV-2 infection.…”
mentioning
confidence: 99%
“…Foi observado, também, um perfil hormonal alterado, que demonstra resistência persistente à insulina, onde pacientes que se recuperam de Covid-19 apresentaram perfil hormonal semelhante aos indivíduos com tipo II (Darif, et al, 2021). SARS-COV-2 infecta as células beta-pancreáticas, promovendo hiperestimulação e funcionamento aberrante, fenômenos detectados em pacientes que se recuperam do Covid-19, o que pode, eventualmente, esgotar essas células culminando em morte celular (Sen, et al, 2021).…”
Section: Resultsunclassified
“…83 Other studies have reported the expression of high amounts of ACE2 in patients with diabetes, particularly those who were treated with drugs such as angiotensin-converting enzyme inhibitors or angiotensin-receptor blockers. 84,85 The overexpression of ACE2 was suggested to be due to the response from the adaptive immune system to counteract elevated levels of angiotensin-2 and angiotensin-1. By this process, SARS-CoV-2 entrance into cells is facilitated to becomes more severe and fatal in the host cells.…”
Section: Okoduwa Sir Et Al Hypothetic Mechanism Of Diabetes Mellitus ...mentioning
confidence: 99%
“…In another study, SARS-CoV-2 was found to enhance apoptosis of CD4 + T-cells, hence compromising the production of interferon gamma (IFN-γ). 85 Vascular dysfunction and thrombotic complications: Another clinical study found that COVID-19 patients could develop thrombotic diseases like microvascular thrombosis as well as venous or arterial thrombosis. 102 This finding was investigated from a study of necropsy and post-mortem biopsies of persons who died of SARS-CoV-2 infection which found both macro and micro-vascular thrombosis in all the organs analysed.…”
Section: Okoduwa Sir Et Al Hypothetic Mechanism Of Diabetes Mellitus ...mentioning
confidence: 99%